Design, synthesis, and evaluation of peptide‐imidazo[1, 2‐a]pyrazine bioconjugates as potential bivalent inhibitors of the VirB11 ATPase HP0525. (17th June 2021) - Sayer, James R.; Walldén, Karin; Koss, Hans; Allan, Helen; Daviter, Tina; Gane, Paul J.; Waksman, Gabriel; Tabor, Alethea B.
Abstract : Helicobacter pylori ( H. pylori ) infections have been implicated in the development of gastric ulcers and various cancers: however, the success of current therapies is compromised by rising antibiotic resistance. The virulence and pathogenicity of H. pylori is mediated by the type IV secretion system (T4SS), a multiprotein macromolecular nanomachine that transfers toxic bacterial factors and plasmid DNA between bacterial cells, thus contributing to the spread of antibiotic resistance. A key component of the T4SS is the VirB11 ATPase HP0525, which is a hexameric protein assembly. We have previously reported the design and synthesis of a series of novel 8‐amino imidazo[1, 2 ‐a ]pyrazine derivatives as inhibitors of HP0525. In order to improve their selectivity, and potentially develop these compounds as tools for probing the assembly of the HP0525 hexamer, we have explored the design and synthesis of potential bivalent inhibitors. We used the structural details of the subunit–subunit interactions within the HP0525 hexamer to design peptide recognition moieties of the subunit interface. Different methods (cross metathesis, click chemistry, and cysteine‐malemide) for bioconjugation to selected 8‐amino imidazo[1, 2 ‐a ]pyrazines were explored, as well as peptides spanning larger or smaller regions of the interface. The IC50 values of the resulting linker‐8‐amino imidazo[1, 2 ‐a ]pyrazine derivatives, and the bivalent inhibitors, were related to docking studies with the HP0525 crystal structure and to molecular dynamics simulations of the peptide recognition moieties. Abstract : The virulence and pathogenicity of H. pylori are mediated by the type IV secretion system (T4SS). A key component of the T4SS is the hexameric protein assembly VirB11 ATPase HP0525, and small molecule inhibitors of HP0525 have been previously reported. In order to improve their selectivity, and potentially develop these compounds as tools for probing the assembly of the HP0525 hexamer, we report the design, synthesis, and evaluation of potential bivalent inhibitors, using the subunit‐subunit interactions within the HP0525 hexamer to design peptide recognition moieties of the subunit interface.